2007
DOI: 10.1021/es0629561
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Alterations of Single Cells Induced by UV in the Presence of NanoTiO2

Abstract: Nanocrystalline titanium dioxide (nanoTiO2) has been reported to generate reactive oxygen species (ROS) under UV illumination. In our studies, changes in mechanical properties of human skin fibroblasts, exposed to the oxidative stress induced in the presence of nanoTiO2 and UV light, were studied using atomic force microscopy (AFM). The exposure of cells to the action of ROS was performed at low TiO2 concentration (4 microg/mL) and under illumination with low-intensity UVA (8 and 20 mW/cm2) or UVC (0.1 mW/ cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…• OH in the UVA activation of nanocrystalline TiO 2 was provided by atomic force microscopy (AFM) measurements showing a marked decrease in the stiffness of phototreated human skin fibroblasts (201).…”
Section: Oxidation Reactions Mediated By Photosensitizersmentioning
confidence: 99%
“…• OH in the UVA activation of nanocrystalline TiO 2 was provided by atomic force microscopy (AFM) measurements showing a marked decrease in the stiffness of phototreated human skin fibroblasts (201).…”
Section: Oxidation Reactions Mediated By Photosensitizersmentioning
confidence: 99%
“…The elastic properties of leaves were measured using a commercially available device (PSIA XE120, Park Systems, Korea) equipped with the ''liquid cell'' setup (Vileno et al 2007). Standard silicon cantilevers in the conical shape of a probing tip were used in all experiments (NSC36, Park Systems).…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…This process can undergo through the surface of leaves, which leads us to the hypothesis that Cr uptake can alter the mechanical properties of leaves. In the present study, in order to verify this hypothesis, we have used atomic force microscopy (AFM) (Vileno et al 2007) to determine the mechanical properties of C. cophocarpa leaves exposed to 100 lM concentration of Cr(III) and Cr(VI). We have shown an important correlation between Cr(VI), Cr(III) and Ca content in relation to the stiffness of the leaf.…”
Section: Introductionmentioning
confidence: 98%
“…In this capacity, human skin serves as a substrate on which photocatalytic reactions can take place. Several studies have already demonstrated the potential dangers to human skin in contact with reactive 2 ISRN Chemical Engineering oxygen species (ROS) produced by photo-excited nanoparticles [4,[13][14][15][16][17][18][19][20]. To date, few researchers have examined the photocatalytic degradation of volatile or semi-volatile species on sunscreen surfaces.…”
Section: Introductionmentioning
confidence: 99%